Delivering Colloidal Nanoparticles to Mammalian Cells: A Nano–Bio Interface Perspective. Issue 7 (20th January 2014) - Verderio, Paolo; Avvakumova, Svetlana; Alessio, Giulia; Bellini, Michela; Colombo, Miriam; Galbiati, Elisabetta; Mazzucchelli, Serena; Avila, Jesus Peñaranda; Santini, Benedetta; Prosperi, Davide
<x xml:space="preserve">Abstract</x> Understanding the behavior of multifunctional colloidal nanoparticles capable of biomolecular targeting remains a fascinating challenge in materials science with dramatic implications in view of a possible clinical translation. In several circumstances, assumptions on structure–activity relationships have failed in determining the expected responses of these complex systems in a biological environment. The present Review depicts the most recent advances about colloidal nanoparticles designed for use as tools for cellular nanobiotechnology, in particular, for the preferential transport through different target compartments, including cell membrane, cytoplasm, mitochondria, and nucleus. Besides the conventional entry mechanisms based on crossing the cellular membrane, an insight into modern physical approaches to quantitatively deliver nanomaterials inside cells, such as microinjection and electroporation, is provided. Recent hypotheses on how the nanoparticle structure and functionalization may affect the interactions at the nano–bio interface, which in turn mediate the nanoparticle internalization routes, are highlighted. In addition, some hurdles when this small interface faces the physiological environment and how this phenomenon can turn into different unexpected responses, are discussed. Finally, possible future developments oriented to synergistically tailor biological and chemical properties of nanoconjugates to improve the control over nanoparticle transport, which could open new scenarios in the field of nanomedicine, are addressed.